2022
DOI: 10.3389/fsurg.2022.817051
|View full text |Cite
|
Sign up to set email alerts
|

Amputation Predisposes to Higher Cancer-Specific Mortality Than Limb Salvage Surgery in Pediatric Patients With Osteosarcoma of the Limbs: A Propensity Matching Analysis

Abstract: ObjectiveWith the development of osteosarcoma treatment, limb salvage surgery is gradually replacing amputation as the primary surgical option. Most pediatric osteosarcomas of the limbs undergo limb-salvage surgery. We aimed to use propensity score matching (PSM) analysis test the difference in cancer-specific mortality (CSM) between amputation and limb-salvage surgery in pediatric patients with Osteosarcoma of the limbs. PSM is a statistical method used to deal with data from an Observational Study. The PSM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…These nomograms either did not incorporate the surgery-related variable or failed to distinguish between the impact of various surgical methods on survival. Prior surgery-related research for osteosarcoma has only identified survival risk factors after amputation or compared survival rates between amputation patients and limbsalvage patients (14)(15)(16)34). Still, they have failed to differentiate between local and radical resection and have not presented reliable postoperative prognostic models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These nomograms either did not incorporate the surgery-related variable or failed to distinguish between the impact of various surgical methods on survival. Prior surgery-related research for osteosarcoma has only identified survival risk factors after amputation or compared survival rates between amputation patients and limbsalvage patients (14)(15)(16)34). Still, they have failed to differentiate between local and radical resection and have not presented reliable postoperative prognostic models.…”
Section: Discussionmentioning
confidence: 99%
“…Salvage surgery has been more advanced in recent years thanks to advancements in adjuvant chemotherapy research, high-intensity focused ultrasound ablation (HIFU), and computer-aided navigation systems (CANS) (10). However, although both local resection and radical resection are considered salvage surgeries, previous studies have failed to distinguish between the two or develop an effective postoperative predictive model for osteosarcoma patients (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaplan–Meier (K–M) curves and log-rank tests were used to analyze the overall survival of limb OS patients with lung and/or BM, and Cox regression analyses were performed to identify the prognostic factors for lung and/or BM. [ 13 ] Statistical analyses were performed using the Statistical Package for Social Sciences (SPSS) 25.0 (IBM, Armonk, NY), all survival charts were used GraphPad Prism 9 (GraphPad, Inc.). Statistical significance was defined as a 2-tailed P < .05.…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric limb salvage has become a standard surgical treatment method for osteosarcoma and traumatic injury. 1 Pediatric limb reconstruction is more than “replacing like with like,” as it must take into consideration the following: growth preservation in a skeletally immature patient, the reconstructed limb’s functional outcome into adulthood, multiple tissue type reconstruction, joint integrity, and need for appropriate immobilization postoperatively. This adds to the concerns that surround all pediatric reconstruction, including the patient’s emotional and social needs, donor site morbidity, and aesthetic outcome.…”
Section: Introductionmentioning
confidence: 99%